The REBELS ALMA Survey: efficient Ly α transmission of UV-bright z ≃ 7 galaxies from large velocity offsets and broad line widths. Issue 4 (25th October 2022) - Endsley, Ryan; Stark, Daniel P; Bouwens, Rychard J; Schouws, Sander; Smit, Renske; Stefanon, Mauro; Inami, Hanae; Bowler, Rebecca A A; Oesch, Pascal; Gonzalez, Valentino; Aravena, Manuel; da Cunha, Elisabete; et al.
ABSTRACT: Recent work has shown that UV-luminous reionization-era galaxies often exhibit strong Lyman-alpha emission despite being situated at redshifts where the IGM is thought to be substantially neutral. It has been argued that this enhanced Ly α transmission reflects the presence of massive galaxies in overdense regions which power large ionized bubbles. An alternative explanation is that massive galaxies shift more of their Ly α profile to large velocities (relative to the systemic redshift) where the IGM damping wing absorption is reduced. Such a mass-dependent trend is seen at lower redshifts, but whether one exists at z ∼ 7 remains unclear owing to the small number of existing systemic redshift measurements in the reionization era. This is now changing with the emergence of [C ii ]-based redshifts from ALMA. Here, we report MMT/Binospec Ly α spectroscopy of eight UV-bright (MUV ∼ −22) galaxies at z ≃ 7 selected from the ALMA REBELS survey. We detect Ly α in four of eight galaxies and use the [C ii ] systemic redshifts to investigate the Ly α velocity profiles. The Ly α lines are significantly redshifted from systemic (average velocity offset = 223 km s –1 ) and broad (FWHM ≈ 300–650 km s −1 ), with two sources showing emission extending to ≈750 km s −1 . We find that the broadest Ly α profiles are associated with the largest [C ii ] line widths, suggesting a potential link between the Ly α FWHM and the dynamical mass. Since Ly α photons at high velocities transmit efficiently through the z = 7 IGM, our data suggest that velocity profiles play a significant role in boosting the Ly α visibility of the most UV-luminous reionization-era galaxies.